The Importance of Definition in Diagnosing Obesity: A Review of Studies of Children in China - Chen, Shu; Binns, Colin; Zhang, Y. (Sage Science Press, 2012)
The prevalence of childhood overweight and obesity in China has increased in recent decades. However, studies reported from China use several different definitions and growth references, making it difficult to compare the rates of obesity from different regions. It also makes it difficult to establish the extent of secular trends in obesity and to make international comparisons. This article reviews the definitions of childhood obesity used in Chinese studies published over the past 10 years. The majority (79%) of the Chinese studies used a definition of >120% of the mean value of the National Center for Health Statistics reference population to diagnose childhood obesity. Only 7 studies (9%) conducted in China measured childhood obesity using age-specific and sex-specific body mass index (BMI) cutoffs, including International Obesity Task Force cutoffs, Centers for Disease Control 2000 and World Health Organization 2006 BMI curves, and Chinese BMI curves. It is important that a consistent and applicable definition is used and all studies accurately define the obesity with growth reference, cutoff criteria, sample selection, and age distribution. The use of sex-specific and age-specific BMI cutoffs should be considered when undertaking future studies of obesity in Chinese children.